2018
DOI: 10.1111/cbdd.13182
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of 3,4,5‐trihydroxypiperidines and their N‐ and O‐derivatives

Abstract: 3,4,5-Trihydroxypiperidines belong to the family of 1,5-dideoxy-1,5-iminosugar natural products and are structural analogues of pentose monosaccharides in the pyranose form. The biological activities of these apparently structurally simple molecules and their N- and O-alkylated and -arylated derivatives are no less remarkable than their C-6 hydroxymethyl counterparts of the hexoses (such as 1-deoxynojirimycin, DNJ). Their biological profiles indicate that the hydroxymethyl branch is crucial to neither potency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Previous studies have shown that the N -alkylated derivative of DGJ N -nonyl-DGJ ( 2 , Figure 1 ) is able to rescue the intracellular activity of mutant β-Gal in GM1-gangliosidosis patient fibroblasts, thus highlighting the potential of PC therapy for patients with brain pathologies [ 15 , 16 ]. In addition, several azasugars, carbohydrate analogues in which nitrogen formally replaces the anomeric carbon, have shown interesting biological activities, as recently reviewed by Simone and coworkers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the N -alkylated derivative of DGJ N -nonyl-DGJ ( 2 , Figure 1 ) is able to rescue the intracellular activity of mutant β-Gal in GM1-gangliosidosis patient fibroblasts, thus highlighting the potential of PC therapy for patients with brain pathologies [ 15 , 16 ]. In addition, several azasugars, carbohydrate analogues in which nitrogen formally replaces the anomeric carbon, have shown interesting biological activities, as recently reviewed by Simone and coworkers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have explored the potential biological activities of several similar iminosugars, including 1-Deoxynojirimycin (DNJ) from mulberry and ido-BR1 from cucumber. Prichard et al [ 21 ] reviewed several iminosugar derivatives with reported activities including glycosidase inhibition, and immunosuppressant, antibacterial, antiviral and anti-inflammatory effects. The iminosugar found in mulberry, DNJ, has garnered interest for antihyperglycemic, anti-obesity, and anti-viral biological activities [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The installation of various functionalities via N-and/or O-alkylation has been shown to impart improved biological profiles and potencies to iminosugars (Š está k et al, 2018;Prichard et al, 2018;Simone et al, 2012;Sayce et al, 2016, Woodhouse et al, 2008Johnson & Houston, 2002). Diminishing the number of synthetic steps to the iminosugar building blocks that are precursors to their alkylated congeners is advantageous.…”
Section: Chemical Contextmentioning
confidence: 99%